The effect of input limiting on linear and nonlinear filters for the removal of impulsive noise - Sharifah Masniah, Wan Masra; Muhammad, M.S.; Sapawi, R. (IEEE, 2010)
This paper investigates the effects of input limiting on the performance of linear and nonlinear filters when the input signal is contaminated by impulsive noise modeled as an alphastable (!-stable) random process. The nonlinear filters chosen are from the median family filters: median and recursive median filter, and Wiener filter from the linear filter group. The hypothesis being tested in this paper is that front-end limiting will increased the performance of median filter when the noise was extremely impulsive. Each image has been analyzed for four impulsive noise parameter values, ! = 2, 1.5, 1, and 0.5 which cover a range of noise behaviors from Gaussian, through Cauchy, to impulsive. One method of handling very large impulses is to incorporate in the receiver over-voltage protection in the form of an analog limiter which clips the received signal before the filtering process. The simulation results obtained suggest that the front-end limiting enhances the performance of median filters in dealing with images, where it eliminates the highly impulsive noise while preserving useful detail in the image.